COMPARATIVE ASSESSMENT AND PREFERENTIAL HOST-PLANT OF CYLAS PUNCTICOLLIS BOH. [COLEOPTERA:Brentidae] Damage Potential on Gossypium Hirsutum L. And Ipomoea Spp. At Sangere, Nigeria. Issue 2 (June 2014) - M., A.; ONU, ONU; I., I.
No abstract available